The Health and Well-Being of Caregivers of Technologically Dependent Children - Yoke Hwee Chan MBBS, MRCP, MMed, MBA; Carmen Zhi-Ruo Lim MD, BEng; Dianne Bautista BSc, MSc, PhD; Rahul Malhotra MBBS, MD, MPH; Truls Østbye MD, MPH, PhD, FFPH (SAGE Publishing, 2019)
Caregivers of technology-dependent children face considerable responsibilities. This study examined the association of 2 child-related stressors-functional status and use of mechanical ventilator-with 2 domains of family caregiver well-being-depressive symptoms (Center for Epidemiologic Studies Depression Scale [CES-D]) and health-related quality of life (HRQOL) and family function (PedsQL Family Impact Module). The secondary objective was to determine whether these associations were moderated by caregiver-perceived social support. Structured interviews were conducted with 88 primary family caregivers of technology-dependent children in Singapore. Hierarchical multiple regression was used to assess the primary and secondary objectives. A total of 44.3% of caregivers were at high risk of clinical depression. Moderately poor child functional status was associated with more caregiver depressive symptoms. Perceived social support moderated this association. Family caregivers of technology-dependent children have high levels of depressive symptoms and relatively poor HRQOL and family functioning. Enhancing caregivers' social support is important for their well-being.